Fractal Ion Acoustic Waves of the Space-Time Fractional Three Dimensional KP Equation - Abdou, M. A.; Owyed, Saud; Ray, S. Saha; Chu, Yu-Ming; İnç, Mustafa; Ouahid, Loubna (Wiley, 2020)
Methods known as fractional subequation and sine-Gordon expansion (FSGE) are employed to acquire new exact solutions of some fractional partial differential equations emerging in plasma physics. Fractional operators are employed in the sense of conformable derivatives (CD). New exact solutions are constructed in terms of hyperbolic, rational, and trigonometric functions. Computational results indicate the power of the method.
Keywords: Numerical-Simulation; Solitary Waves; Plasma; Model